2009
DOI: 10.1515/jgt.2008.066
|View full text |Cite
|
Sign up to set email alerts
|

The aspherical Cavicchioli–Hegenbarth–Repovš generalized Fibonacci groups

Abstract: Abstract. The Cavicchioli-Hegenbarth-Repovš generalized Fibonacci groups are defined by the presentations G n ðm; kÞ ¼ hx 1 ; . . . ; x n j x i x iþm ¼ x iþk ð1 c i c nÞi. These cyclically presented groups generalize Conway's Fibonacci groups and the Sieradski groups. Building on a theorem of Bardakov and Vesnin we classify the aspherical presentations G n ðm; kÞ. We determine when G n ðm; kÞ has infinite abelianization and provide su‰cient conditions for G n ðm; kÞ to be perfect. We conjecture that these are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…In connection with this and with Question 5 of [1] we note that this behaviour cannot occur for the groups H n .m; k/ (of the introduction) when they are finite (by [14], [15]), and that there are no recorded examples of it when they are infinite.…”
Section: Preliminariesmentioning
confidence: 64%
See 3 more Smart Citations
“…In connection with this and with Question 5 of [1] we note that this behaviour cannot occur for the groups H n .m; k/ (of the introduction) when they are finite (by [14], [15]), and that there are no recorded examples of it when they are infinite.…”
Section: Preliminariesmentioning
confidence: 64%
“…Using Theorem 2 of [14] and Theorem 3.2 of [10] we can obtain (the analogous result to Corollary 4.3) that the converse holds in many cases. For the interested reader we now state such a result where, for simplicity, we consider only the 'strongly irreducible' cases (see [14]). …”
Section: Corollary 43mentioning
confidence: 65%
See 2 more Smart Citations
“…More recently the groups R(2, n, k, h) -the so-called Cavicchioli-Hegenbarth-Repovš groups G n (h, h + k) -have been of interest for their algebraic and topological properties (see [3], [9]). With the exception of two unresolved cases the finite groups R(r, n, k, h) were classified in [17], [18], [10] and the present paper arose from a desire to classify the finite semigroups T (2, n, k, h). In doing so we found that the asphericity methods used in [3], [17] are effective in the more general setting and can be combined with the Adjan graph and semigroup rewriting techniques of [6], [7] to classify the finite semigroups T (r, n, k, h) in terms of the finite groups R(r, n, k, h).…”
Section: Introductionmentioning
confidence: 99%